Minimally Invasive Posterior Stabilization Improved Ambulation and Pain Scores in Patients with Plasmacytomas and/or Metastases of the Spine. (5th September 2011) - Schwab, Joseph H.; Gasbarrini, Alessandro; Cappuccio, Michele; Boriani, Luca; De Iure, Federico; Colangeli, Simone; Boriani, Stefano
Abstract : Background . The incidence of spine metastasis is expected to increase as the population ages, and so is the number of palliative spinal procedures. Minimally invasive procedures are attractive options in that they offer the theoretical advantage of less morbidity. Purpose . The purpose of our study was to evaluate whether minimally invasive posterior spinal instrumentation provided significant pain relief and improved function. Study Design . We compared pre- and postoperative pain scores as well as ambulatory status in a population of patients suffering from oncologic conditions in the spine. Patient Sample . A consecutive series of patients with spine tumors treated minimally invasively with stabilization were reviewed. Outcome Measures . Visual analog pain scale as well as pre- and postoperative ambulatory status were used as outcome measures. Methods . Twenty-four patients who underwent minimally invasive posterior spinal instrumentation for metastasis were retrospectively reviewed. Results . Seven (29%) patients were unable to ambulate secondary to pain and instability prior to surgery. All patients were ambulating within 2 to 3 days after having surgery (P = 0.01 ). The mean visual analog scale value for the preoperative patients was 2.8, and the mean postoperative value was 1.0 (P = 0.001 ). Conclusion . Minimally invasive posterior spinal instrumentation significantly improved pain and ambulatory status in this series.